2021
DOI: 10.2147/dmso.s223618
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Patients with Type 1 Diabetes: Links, Risks and Management Challenges

Abstract: Obesity affects large numbers of patients with type 1 diabetes (T1D) across their lifetime, with rates ranging between 2.8% and 37.1%. Patients with T1D and obesity are characterized by the presence of insulin resistance, of high insulin requirements, have a greater cardiometabolic risk and an enhanced risk of developing chronic complications when compared to normal-weight persons with T1D. Dual treatment of obesity and T1D is challenging and no specific guidelines for improving outcomes of both glycemic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 184 publications
(174 reference statements)
0
33
0
Order By: Relevance
“…And among all of those therapies, personalized precision medicine may contribute to the medical management and care of obesity patients. 79 …”
Section: Therapeutic Targetmentioning
confidence: 99%
“…And among all of those therapies, personalized precision medicine may contribute to the medical management and care of obesity patients. 79 …”
Section: Therapeutic Targetmentioning
confidence: 99%
“…The authors of The SWEET Registry demonstrated that switching from the multiple daily insulin injection to the continuous subcutaneous insulin infusion is significantly associated with an improvement in glycemic control but also with an increase in BMI in more than 4,000 youths with T1D ( 15 ). Interestingly, there are findings suggesting that in cases of co-occurring obesity and type 1 diabetes, making some changes to current therapy and using new long acting analogues as basal insulins, such as detemir, degludec and glar-300 may slightly prevent the weight gain associated with intensive insulin therapy ( 83 ). However, the study by Baskaran et al.…”
Section: Obvious and Less Obvious Causes Of Obesity In Type 1 Diabetesmentioning
confidence: 99%
“…Obesogenic environment with easy availability of processed, high-energy foods, poor dietary habits and sedentary behaviour are the main factors causing obesity in the general population and they contribute significantly to weight gain among patients with type 1 diabetes ( 83 ). It is worth noting that patients with T1D treated with intensive insulin therapy focus more on the amount of carbohydrates in a meal rather than on balanced nutrition.…”
Section: Obvious and Less Obvious Causes Of Obesity In Type 1 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations